Analysis and Experimental Validation of Rheumatoid Arthritis Innate Immunity Gene CYFIP2 and Pan-Cancer - Zhao, ZhenYu; He, ShaoJie; Yu, XinCheng; Lai, XiaoFeng; Tang, Sheng; Mariya M., El Akkawi; Wang, MoHan; Yan, Hai; Huang, XingQi; Zeng, Shan; Zha, DingSheng (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a chronic, heterogeneous autoimmune disease, and its high disability rate will have a serious impact on society and individuals, but there is still a lack of effective and reliable diagnostic markers and therapy targets for RA. In this study, we integrated RA patient information from three GEO databases for differential gene expression analysis. In addition, we also obtained pancancer-related genes from the TCGA and GTEx databases. For RA-related differential genes, we performed functional enrichment analysis and constructed a weighted gene co-expression network (WGCNA). Then, we obtained 490 key genes by intersecting the significant module genes selected by WGCNA and the differential genes. After using RanddomForest, SVM-REF and LASSO three algorithms to analyze these key genes and take the intersection, we found four core genes (BTN3A2, CYFIP2, ST8SIA1, TYMS), based on the four core genes constructed RA diagnosis The nomogram model showed good reliability and validity after evaluation, and the ROC curves of the four genes showed that these four genes played an important role in the pathogenesis of RA. After further gene correlation analysis and immune infiltration analysis, and mouse gene expression validation, we finally selected CYFIP2 as the cut-in gene for pancancer analysis. The results of pancancer analysis showed that CYFIP2 was closely related to the prognosis of patients with various tumors, the degree of immune cell infiltration, as well as TMB, MSI and other indicators, suggesting that this gene may be a potential intervention target for human diseases including RA and tumors.